Effect of Joint Exposure to Psychosocial and Physical Work Factors on the Incidence of Workplace Injuries: Results From a Longitudinal Survey. Issue 11 (7th November 2021) - Colin, Régis; Wild, Pascal; Paris, Christophe; Boini, Stéphanie
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: To analyze the interaction between physical and psychosocial work factors regarding the workplace injuries incidence among 6900 workers out of a longitudinal survey. Methods: Based on responses to questionnaires, we obtained exposure groups respectively for physical factors and for psychosocial factors using hierarchical clustering. We performed multiple Poisson regression model with the workplace injuries incidence during 4 years of follow-up as the outcome and the clusters as the independent variables of interest. Results: High psychosocial exposure had a deleterious effect on workplace injuries incidence, which was no longer significant when adjusting for physical factors. The difference in model-based workplace injuries rates between high and low psychosocial exposures seemed to increase (non-significantly) with increasing physical exposure. Conclusions: The risk of workplace injuries was highest among workers with high physical exposures regardless of the psychosocial exposures.